The influence of dietary and supplemental omega-3 fatty acids on the omega-3 index: A scoping review - Dempsey, Meghan; Rockwell, Michelle S.; Wentz, Laurel M. (Frontiers in Nutrition, 2023)
Introduction The majority of the population do not consume adequate omega-3 fatty acids (n-3 FA), leading to global deficiencies, as evidenced by poor omega-3 status. An indicator of overall n-3 FA status, omega3-index (O3i) ≥8% has been associated with reduced risk of chronic disease, most notably cardiovascular disease. Thus, a synthesis of current research summarizing the effects of n-3 FA intake on O3i is warranted to develop and refine clinical recommendations. The purpose of this scoping review was to evaluate the effect of n-3 FA interventions and estimate sufficient n-3 FA intake to improve O3i to meet recommendations. Methods Search criteria were human studies published in English from 2004 to 2022 that assessed O3i at baseline and following an n-3 FA intervention. Results Fifty-eight studies that met inclusion criteria were identified. Protocols included fish consumption, fortified foods, combined eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) supplements, supplements of single n-3 FA (alpha linolenic acid (ALA), EPA, DHA, etc.), and supplements providing multiple n-3 FA. Dietary supplements varied in chemical composition; the most common were triglycerides or ethyl esters. The lowest supplementation protocol was 100 mg/d, and the largest was 4,400 mg/d EPA and DHA. Supplementation time period ranged from 3 weeks to 1 year. At baseline, three study samples had mean O3i >8%, although many intervention protocols successfully increased O3i. Discussion Generally, the lowest doses shown to be effective in raising O3i to recommended levels were >1,000 mg/d of combination DHA plus EPA for 12 weeks or longer. Supplements composed of triglycerides were more bioavailable and thus more effective than other formulas. Based on the data evaluated, practical recommendations to improve O3i to ≥8% are consumption of 1,000–1,500 mg/d EPA plus DHA as triglycerides for at least 12 weeks.